Empirical Insights Into the Fate of Ammonia in Western U.S. Wildfire Smoke Plumes. Issue 11 (8th June 2021) - Lindaas, Jakob; Pollack, Ilana B.; Calahorrano, Julieta Juncosa; O'Dell, Katelyn; Garofalo, Lauren A.; Pothier, Matson A.; Farmer, Delphine K.; Kreidenweis, Sonia M.; Campos, Teresa; Flocke, Frank; Weinheimer, Andrew J.; Montzka, Denise D.; et al.
Abstract: Wildfires are a major source of gas‐phase ammonia (NH3 ) to the atmosphere. Quantifying the evolution and fate of this NH3 is important to understanding the formation of secondary aerosol in smoke and its accompanying effects on radiative balance and nitrogen deposition. Here, we use data from the Western Wildfire Experiment for Cloud Chemistry, Aerosol Absorption, and Nitrogen (WE‐CAN) to add new empirical constraints on the e‐folding loss timescale of NH3 and its relationship with particulate ammonium ( p NH4 ) within wildfire smoke plumes in the western U.S. during summer 2018. We show that the e‐folding loss timescale of NH3 with respect to particle‐phase partitioning ranges from ∼24 to ∼4000 min (median of 55 min). Within these same plumes, oxidation of nitrogen oxides is observed concurrent with increases in the fraction of p NH4 in each plume sampled, suggesting that formation of ammonium nitrate (NH4 NO3 ) is likely. We find wide variability in how close our in situ measurements of NH4 NO3 are to those expected in a dry thermodynamic equilibrium, and find that NH4 NO3 is most likely to form in fresh, dense smoke plumes injected at higher altitudes and colder temperatures. In chemically older smoke we observe correlations between both the fraction of p NH4 and the fraction of particulate nitrate ( p NO3 ) in the aerosol with temperature, providing additional evidence of the presence of NH4 NO3 and the influence of injection height on gas‐particle partitioning of NH3 . Key Points: We estimate e‐folding loss timescales for ammonia in eight western U.S. smoke plumes from 24 to 4000 min old (median = 55 min) Ammonium nitrate formation is favorable in fresh, dense plumes injected higher into the troposphere, nitric acid is normally limiting Observed ammonium and nitrate fractions increase with lower temperatures in medium (1–3 days) and old (>3 days) chemical aged smoke